Ecological Risk Assessment of Inorganic Arsenic and Mercuric Fungicides Through Biological Tools - Minahil Sikandar; Ayesha Mohsin; Alina Malik (CV. Literasi Indonesia, 2023)
This review discusses the use, mode of action, biomarkers, and bioindicators of inorganic arsenic and mercuric fungicides, as well as their effects on the environment and human health. The most prevalent indicator of exposure to arsenic is the measurement of total arsenic in urine. Biomarkers of exposure for arsenic and inorganic fungicides incudes the analysis of hair, urine, blooda and nails. Bio indicators are species or group of species that are used to indicate adverse effect of contamination. Freshwater fish species act as a very good bio indicator for inorganic arsenic. Tree bark, rice fields and sea birds could be a valuable indicator of inorganic arsenic contamination. Black Piranha, fish and earthworms are an ideal bio indicator of inorganic mercury. Inorganic arsenic compounds are known to be highly carcinogenic and toxic compounds. Mercuric fungicide is very toxic when inhaled by humans or animals it causes severe health issues and when absorbed by plants it retards their growth. To estimate the daily dose of arsenic exposure to humans through absorption, ingestion and other pathways, Average daily dose is implemented by using two equations from the US EPA. To determine the ecological risk assessment a simplified equation was proposed by FDA i.e. HQ = E/RfD. Overall, the review emphasizes the need for heightened awareness, regulation, and alternative approaches to fungicide use, with a focus on minimizing the use of inorganic arsenic and mercuric fungicides to safeguard the environment and promote sustainable agricultural practices.